The Influence of Parental Involvement and Education Policy on Student Achievement in High Schools in NongChok District, Bangkok, Thailand - Saralee Yosai (Magister Administrasi Publik, 2016)
The purpose of this research is to study the influence of parental involvement in education related activities on student achievement in high schools in NongChok District, Bangkok, Thailand. To compare the influence that parental involvement has on student achievement as well as analyze the joint influence of parental involvement and education policy on student achievement, parents are categorized in accordance with demographic characteristics. The population in the comprised parents who have children that are currently studying in public high schools in NongChok district, Bangkok, Thailand. A non-random sampling method was used in determining the sample of respondents used in the survey. The calculated sample size was 210 respondents. Data were collected using structured questionnaire which had 0.88 reliability. Determining demographic characteristics was based on descriptive statistics (percentage, mean, and Standard Deviation; while One-way ANOVA, and Multiple Linear Regression analysis techniques were used to analyze the data. Study results indicated that 60.5 percent of respondents were married mothers (79.5 percent), had high school education attainment or equivalent to (51.4 percent), worked as employees (43.8 percent), earned below or equivalent to 150,000 Baht per year (44.3 percent), and worked less than or equal to 8 hours per day (71.9 percent). Testing of hypotheses showed that the involvement of parents in students’ education of parents takes various forms; type of the parents had a statistically significant influence on students’ achievement at 0.01 level. The results of the multiple linear regression analysis indicated that education policy had significantly influence on students’ achievement at 0.01 level, while parental involvement did not show statistically significant relationship with students’ achievement.